Journal of Greek Archaeology Volume 6: Editorial - Bintliff, John (Journal of Greek Archaeology, 2021)
Our latest volume maintains our goal to cover the broad chronological spread of Greek Archaeology, ranging from a new review of the Mesolithic occupation at Theopetra, one of the most important hunter-gatherer sites in Greece, to a detailed analysis of how the distribution of Middle Byzantine churches in the Peloponnese enlightens us into the evolution of human settlement and land use.